ANALISIS FUNGSIONALITAS APLIKASI E-COMMERCE SEPATU CONVERSE - Azril Ardiansyah; Muhammad Zikri Ardiyansyah (Journal of Information Systems and Business Technology, 2025)
Advances in information technology have driven changes in the world of commerce, including the development of e-commerce as a means of modern buying and selling. This research aims to analyze the functionality of web-based e-commerce applications for the sale of Converse shoes. The application is developed using the Waterfall method with the stages of requirements analysis, system design, implementation, and testing. Testing is done using the Black Box Testing method to evaluate functions from the user's perspective. The test results show that most of the main features, such as login, registration, product management, transactions, and customer reviews, run well. Some shortcomings were found in the system feedback that did not display notification messages on certain features. But overall, the application is considered functional, user-friendly, and feasible to use as a digital sales platform for Converse shoes.